Facile microwave-mediated green synthesis of non-toxic copper nanoparticles using Citrus sinensis aqueous fruit extract and their antibacterial potentials - Jahan, Israt; Erci, Fatih; Isildak, Ibrahim (ELSEVIER, 2021)
This study focuses on the utilization of orange (Citrus sinensis) fruit extract for microwave mediated green synthesis of copper nanoparticles for the first time. After completion of the synthesis cycles, the presence of a maximum peak at the wavelength of 560 nm by UV-vis spectroscopy indicated the formation of CuNPs. FTIR spectrum identified the functional biomolecules of the orange juice extract, responsible for the bioreduction, stabilization of copper nanoparticles. Scanning Electron Microscopy (SEM) indicated the presence of globular shaped nano-sized copper particles with smooth surfaces whereas Energy Dispersive X-ray Spectrometry (EDX) confirmed the presence of copper, carbon and oxygen atoms with the amount of 77.68%, 17.55% and 4.77%, respectively. Transmission Electron Microscopy (TEM) illustrated that the CuNPs are morphologically round in shape with the distribution range of 6.93 nm-20.70 nm in diameter. X-ray diffraction (XRD) analysis revealed the presence of face-centered cubic crystalline structures of copper nanoparticle, and Zeta potential analysis confirmed their high stability by showing the strong negative potential value (-25.60 mV). Moreover, these biosynthesized copper nanoparticles displayed their efficiency in controlling the growth of the bacteria, i.e., Escherichia coli and Staphylococcus aureus. The results revealed their non-cytotoxic nature on the L929 mouse fibroblast cell line through XTT cell viability assay. All these studies indicated that CuNPs synthesized by orange extract have the potential to serve as a green nanomaterial for biomedical applications.
Keywords: Citrus sinensis; Microwave; Green synthesis; Copper nanoparticles; Antibacterial activity; Cytotoxicity; OXIDE NANOPARTICLES; ANTIMICROBIAL ACTIVITY; SILVER; BIOSYNTHESIS; METAL; Pharmacology & Pharmacy